Maternal Local Food Literacy and Food Regulation as Determinants of Nutritional Status in Children Under Five: A Study in North Aceh, Indonesia - Fauziah Fauziah; Fitriani Fitriani; Syamsul Bahri (Journal of Health and Nutrition Research, 2026)
The nutritional status of children aged 0 – 59 months remains a major public health concern in Indonesia, particularly in rural areas. Although local foods are often rich in essential nutrients, their utilization is frequently constrained by limited maternal food literacy. This study aimed to examine the association of maternal local food literacy and food regulation on the nutritional status of children under five in Keude Amplah, Nisam District. This study employed a quantitative analytical design with a cross-sectional approach. A total of 87 mothers with children aged 0–59 months were selected using proportional random sampling across 12 villages to ensure geographical representation. Data were collected using structured questionnaires assessing maternal local food literacy and food regulation, along with anthropometric measurements of children’s nutritional status based on weight-for-age and height-for-age indicators. Data analysis was conducted using the Chi-square test and multiple linear regression. The Chi-square analysis revealed a significant association between maternal local food literacy and the nutritional status of children under five (p < 0.001), as well as between food regulation and nutritional status (p < 0.001). Descriptive results showed that 12.6% of the children were stunted and 17.2% were undernourished. Multiple linear regression analysis indicated that maternal local food literacy (B = 0.482; p < 0.001) and food regulation (B = 0.635; p < 0.001) were significant predictors of child nutritional status, explaining 72.2% of the variance (R² = 0.722). The study concludes that maternal food literacy and regulatory support are critical determinants of child health; therefore, local food literacy should be integrated into community health programs, such as posyandu (a community-based health posts) to optimize child nutritional outcomes